Effectiveness of Community Service Activities in Increasing Teacher Insight and Motivation in the Use of Geogebra-Based Learning Media in Mathematics Learning - Puspitasari, Nitta; Sofyan, Deddy; Sundayana, Rostina; Afriansyah, Eka Aldila; Ciski, Dina; Zhesi, Zhesi; Damayanti, Desi; Lesmana, Andi (Fakultas Kewirausahaan Universitas Garut, 2023)
The usefulness of mathematics in the 21st century is increasingly felt by society. Therefore, mathematics is increasingly needed by everyone and by society as a whole. In the current industrial era 4.0, there is interaction between humans and machines, especially computers. One computer application that can be used in mathematical problems is GeoGebra. GeoGebra is dynamic software for mathematics, contains interconnected Geometry and Algebra features, and is very helpful in understanding and facilitating the teaching and learning process of mathematics. The aim of this research is to find out how mathematics teachers perceive the use of GeoGebra-based learning media in mathematics learning. The research method is descriptive qualitative. The research population was all teachers from an educational foundation in Pamengpeuk District, Garut Regency, participants in a workshop on the use of GeoGebra-based learning media in mathematics learning. This workshop activity is a community service activity. The results of this research conclude that community service activities through workshops on the use of GeoGebra-based learning media in mathematics learning are effective in increasing teachers' insight and motivation to use the GeoGebra application in mathematics learning.